Felkészítés a virtuális üzleti világra - Dancsházy, Kinga; Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The goal of the project developed under the Leonardo da Vinci programme, "SME’s e-learning to e-work efficiently" was to provide a practical and useful support for the preparation of e-managers and e-workers of small and medium-sized enterprises working in a virtual environment and to be able to be useful e-team members of virtual teams. To achieve the goals the following tasks were carried out: (1) Specification of needs; (2) Development of the on-line toolkit; (3) Development of the training material; (4) Training the e-tutors; (5) Development of the testing methodology; (6) Pilot testing on the target group; (7) Accreditation of the modules; (8) Continuous dissemination and promotion activities. The three main products of the project are the sectoral survey report, the on-line toolkit and twelve e-learning modules. All products arc developed to support e-work in a virtual environment.